Testing procedure for determining isothermal properties of the freight car body intended for the transport of perishable freights in the absence of specialized climate chamber - D. O. Davydov (Вестник Научно-исследовательского института железнодорожного транспорта)
According to the Rules for the transport of perishable freights by rail, isothermal vehicles must comply with the provisions of the Agreement on the international transport of perishable foodstuffs and on special vehicles intended for this transport (ATP). The article proposed a technique for determining isothermal properties of the body of freight cars intended for the transportation of perishable freights by testing in the absence of a specialized climate chamber. The requirements of the ATP to the testing conditions are analyzed and the parameters that in the absence of a specialized climate chamber are impossible or difficult to perform are considered in detail. For each such parameter, a sequence of actions has been developed to bring the actual test conditions closer to the requirements of the ATP, and methods that allow adjusting the test results are justified taking into account the reduction of the specified parameters to the requirements of the ATP.The proposed methodology of heat engineering tests of isothermal cars will allow:• conduct heat engineering tests of thermos and refrigerated cars with high accuracy of obtaining the final result and the basic requirements of ATP;• create a mechanism for control and examination of isothermal cars and containers under comparable conditions.The methodology is of interest to organizations involved in the thermotechnical testing of isothermal cars, as well as for organizations entrusted with the functions of monitoring the thermotechnical parameters of isothermal cars.